Розвиток промисловості регіонів Придніпров’я під час війни та потреба в її інноваційній модернізації - Antoniuk, Valentyna P.; Lyashenko, Viacheslav I. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The article analyzes the dynamics of industrial activity in the regions of the Middle Dnieper (Dnipropetrovsk, Zaporizhzhia, Kirovohrad, Poltava, and Cherkasy Oblasts) from 2020 to 2023. These regions played a significant role in Ukraine's industrial complex before the war, which substantially worsened their economic situation. Significant destruction, losses, production curtailment, and relocation are shaping a new economic reality for regional development and impacting industrial development opportunities.The aim of the article is to analyze the dynamics and outcomes of the manufacturing industry in the Dnieper regions amidst the war and regional industrial development policy, considering the need for its innovative modernization.The analysis of the number of active business entities in the regions overall and within the industry showed a gradual adaptation of businesses to risks and a resumption of enterprise activity. However, the volume of sold products in comparable prices decreased, indicating a decline in business performance during the war. A positive aspect was the increased share of manufacturing output in the total sales volume of the regions. A negative trend was identified: a decreasing share of high-tech industrial sectors in the overall industrial structure of the Dnieper regions, which deteriorates the technological level of their economies. The analysis of development programs and tasks for the studied Dnieper regions for 2025 revealed insufficient attention to ensuring the development of the regional industrial complex in most program documents. Furthermore, innovative development and the adoption of new technologies are not currently prioritized in regional policy. This does not align with the necessary technological modernization of the Dnieper regions' economies, crucial both during the war and for post-war recovery. Directions and measures for improving regional policy aimed at the needs of innovative modernization of the regional economy are proposed. The language of the article is Ukrainian.